Quality Public Spaces in High Areas of Lima. Short Cable Cars Sustainable Connectivity Solution, Peru 2026 - Juan Miguel Guerrero Orbegozo, Filoter Tello Yance (Journal of Intelligent Decision Making and Information Science, 2026)
The rapid growth of modern cities has brought with it serious challenges related to mobility, accessibility to different territories and the availability of good quality public spaces, especially in peripheral areas with difficult terrain. In this sense, the purpose of this study is to examine the academic production on sustainable connectivity alternatives and their link with the improvement of accessibility in cities and the quality of public spaces in difficult urban environments. To this end, a systematic literature review was carried out following the PRISMA protocol, consulting the scientific databases Scopus and Web of Science. Through this search strategy, 29 relevant scientific articles were initially identified. After eliminating duplicates and applying inclusion and exclusion criteria, 13 scientific articles published in 2025 were finally selected and thoroughly analyzed. The findings show that recent literature underscores the need to bring together urban planning, territorial accessibility, multimodal mobility and the quality of the built environment to move towards urban mobility systems that are sustainable. In addition, the studies reviewed indicate that transport infrastructures can serve as catalysts for urban transformation by being connected to the development of public spaces and improving territorial connectivity. Within this context, short-distance urban cable cars are presented as a viable solution to improve connectivity in urban areas with complicated terrain, such as the highlands of Lima, facilitating access to urban services and favoring the integration of peripheral neighborhoods. It is concluded that the implementation of this type of proposal should be approached from a comprehensive perspective that combines transport infrastructure, territorial planning and development of quality public spaces, with the aim of promoting urban mobility models that are more sustainable and inclusive.